ANALISA PENYEBAB KEMACETAN TERHADAP ARUS LALU LINTAS JALAN LINTAS SUMATERA PANGKALAN BALAI - Sarwandy, M. Hijrah Agung; Royan, Noto (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2023)
This study focuses on survey studies on the analysis of the causes of congestion on the km15-km18 road sections. To find out the analysis of the causes of congestion, road capacity, vehicle volume, level of service, determine resolution of problems, and analyze average daily traffic by conducting field surveys for seven days. This research was conducted in 1 research segment, namely: on the Sumatran crossroads at Pangkalan Balai Km15-km18 "Analysis Of The Causes Of Congestion On Traffic Flow Of The Sumatra Traffic Road Pangkalan Balai". The purpose of this research is to determine the effect of narrowing on traffic performance on the Sumatra Highway Km 15 – Km 18. The research implementation method used is by means of an Average Daily Traffic (LHR) survey, namely collecting data directly at the research location.  Based on the results of the analysis, it was found that the side barriers included high, the volume of vehicles with inadequate road capacity.